Pelatihan Pembuatan Produk berbasis Jantung Pisang pada Ibu-Ibu PKK dan Dasa Wisma Desa Dutohe Barat - Mardjan Paputungan; Nurhayati Bialangi; Hamid Majelis (Damhil: Jurnal Pengabdian kepada Masyarakat, 2022)
West Dutohe Village is located in Kabila District, Bone Bolango Regency, Gorontalo Province, has a plantation area that is generally planted with banana trees so that it becomes a superior commodity for the village community. Banana liver was chosen as a product because of its very abundant availability in the village of West Dutohe. The PKK consists of 30 people who are interested in becoming entrepreneurs, but due to lack of direction and training, this business group is less productive in producing products that are worth selling. The absence of innovation in processing technology into various processed banana heart products of economic value such as sausages, meatballs, nuggets, and shredded banana liver is constrained by lack of knowledge and motivation. The Community Service Program in West Dutohe village aims to increase the motivation of mothers to become independent entrepreneurs through appropriate technology in the field of banana liver-based food processing. Training methods for processing various food products based on banana liver such as sausages, meatballs, and nuggets. The implementation of activities in training on production and innovation of banana liver-based products is very cooperative between trainers and partners, especially PKK mothers. The insights of partners and village officials are open and eager for the continuation of this program in the village of West Dutohe. The advantages of various liver-based processed products are very powerful because there is nothing similar in other areas so this product can create a novelty and culinary peculiarity in the western Village of Dutohe